1992
DOI: 10.1017/s0016756800008463
|View full text |Cite
|
Sign up to set email alerts
|

A new record of early Silurian land plant spores from the Paraná Basin, Paraguay (Malvinokaffric Realm)

Abstract: The first conclusive evidence for Silurian rocks in the Parana Basin, Brazil, was reported in 1985. This evidence was based on organic-walled microfossils, principally spore tetrads, and associated phytoplankton (' acritarchs' and prasinophytes), the first recovered from the Vila Maria Formation on the northeastern rim of the Basin. The spore assemblage was typical of Gray's Microfossil Assemblage Zone I; size-frequency data for the tetrads suggested an early Silurian (early Llandovery; Rhuddanian) age. We now… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…The Vargas Pefia Formation in east Paraguay, or the Vila Maria Formation and its equivalents in south Brazil, are now generally considered as Llandovery s.l. in age (Wood and Miller, 1991;Gray et al, 1992;Borghi et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The Vargas Pefia Formation in east Paraguay, or the Vila Maria Formation and its equivalents in south Brazil, are now generally considered as Llandovery s.l. in age (Wood and Miller, 1991;Gray et al, 1992;Borghi et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Such assemblages are known from South America in Brazil and Paraguay (Gray 1991;Gray et al 1985Gray et al , 1992Laranjeira et al 1997;Melo 1997;Melo & Steemans 1997;Mizusaki et al 1992;Steemans 2000;Steemans & Pereira 2000), from North America (Strother & Traverse 1979, Miller & Eames 1982, Duffield 1985, Johnson 1985, from Europe in Belgium (Steemans 2001), Bulgaria (Lakova et al 1992), the Czech Republic (Vavrdová 1984(Vavrdová , 1988(Vavrdová , 1989, United Kingdom (Burgess 1991, Wellman 1996, from Asia in China (Wang et al 1997), Turkey (Steemans et al 1996), Saudi Arabia , and from north Africa in Libya (Richardson 1988).…”
Section: Cryptosporesmentioning
confidence: 88%
“…Littoral to nearshore conditions for the association are proposed in the second assemblage of Moussegouda, but also in the samples from KW-2 in the Kufra Basin, is consistent with significant freshwater input. This is supported by the presence of forms such as Moyeria cabottii regarded to be of freshwater origin (Gray & Boucot 1989, Dorning & Harding 1998. The good representation of miospores, and tubular structures (Tortotubus protuberans) believed to derive from nematophytes (Wellman 1995), is further evidence of deposition in a nearshore shallow water marine environment.…”
Section: A1mentioning
confidence: 95%
“…Many studies (Gray 1992;Richardson 1988;Steemans 1999a, b) reported possible cryptospores from Middle and late Ordovician. The recorded possible cryptospore assemblages from deposits older than Caradoc are either naked or enclosed within a thin, smooth or variously ornamented envelops.…”
mentioning
confidence: 99%
“…However, (Wellman and Richardson 1993;Strother and Traverse 1979;Richardson 1992;Gray et al 1992;Wellman and Gray 2000;Steemans 1999b) believe that the structure and morphology of these early miospores are atypical comparing with existing miospores of younger ages, therefore some times, embryophyte miospores been used as cryptospores. This is due to that the widely spread vegetation was of restricted diversity and diminutive evolutionary change.…”
mentioning
confidence: 99%